Toxicology of aquatic pollution : physiological, molecular and cellular approaches - Taylor, E. W. (Society for experimental biology seminar series 57, 1996)
When this book was first published in 1996, the pollution of the earth's freshwater habitats was, as it is now, a topic of major concern